2015
DOI: 10.1136/sextrans-2015-052270.276
|View full text |Cite
|
Sign up to set email alerts
|

P04.22 Sex partner meeting places over time among newly hiv diagnosed men who have sex with men (msm) in baltimore, maryland

Abstract: outcomes, and interviewer-administered alcohol consumption questions, at age 26, 32 and 38 years. Results Response level was >90% at each assessment. At 38, drinking before or during sex in the previous year was common (8.2% of men; 14.6% of women reported "usually/always"), and unwanted consequences were reported by 13.5% of men and 11.9% of women, including regretted sex or failure to use contraception or condoms. Frequent heavy drinkers were more likely to "use alcohol to make it easier to have sex" and reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In addition, it is notable that the majority of nominated sex partner meeting places (53.1%) were online venues. Our prior work showed increasing trends in nominations of online sex partner meeting places, but also suggested that physical places remained important and highly connected to online spaces [22,34]. Our current work suggests that sex partner meeting venues are dynamic and for MSM, may be increasingly online.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In addition, it is notable that the majority of nominated sex partner meeting places (53.1%) were online venues. Our prior work showed increasing trends in nominations of online sex partner meeting places, but also suggested that physical places remained important and highly connected to online spaces [22,34]. Our current work suggests that sex partner meeting venues are dynamic and for MSM, may be increasingly online.…”
Section: Discussionmentioning
confidence: 54%
“…Venues were classified into six typologies: internet/app (i.e. online), bar/club, street/park/neighborhood, market/mall, or other [34]. Venues were also classified based on the diagnoses of the individuals reporting the venue.…”
Section: Venue-level Measuresmentioning
confidence: 99%
“…Recently, online spaces have increasingly been used by MSM for social and sexual networking 8,9 especially among young MSM. 10 Geo-social networking apps (GSN apps) have become particularly popular.…”
Section: Purposementioning
confidence: 99%
“…8,11 From 2010 to 2015, nomination of internet-based venues as sex partner meeting places in partner services interview (eg, websites, social media platforms, and geosocial networking [GSN] applications) increased from 21% to 43% among MSM in Baltimore diagnosed with syphilis and/or HIV; GSN apps specifically increased from 5% to 26% during that time. 9 In 2015, GSN apps accounted for 60% of all internet-based venues reported by newly diagnosed HIV-infected MSM. These findings suggest that GSN apps could be virtual spaces connected to ongoing HIV/STI transmission networks, which could place users at risk of acquisition and be important access points for outreach activities prioritizing at-risk populations.…”
Section: Purposementioning
confidence: 99%
“…In addition, as technology advances and the use of online venues to meet sex partners continues to proliferate, 15 especially among MSM, 16 it is crucial to understand how online and offline venues differ, and how these different venues influence sexual health outcomes. This understanding is essential to better inform behavioral interventions to attenuate HIV transmission among MSM.…”
Section: Introductionmentioning
confidence: 99%